Stereoselective Copolymerization of Olefin with Polar Monomers to Access Stereoregular Functionalized Polyolefins - Mu, Hongliang; Jian, Zhongbao (Organic Materials, 2022)
Introducing polar functionalities to polyolefins such as polyethylene and polypropylene is highly desirable for improving physical properties of the otherwise non-polar material. The synthesis of stereoregular functionalized polyolefins, however, has been a relatively underdeveloped area compared to that of functionalized polyethylene because of the lack of suitable catalysts that tolerate polar groups while possessing stereoselectivity. This review summarizes recent advances concerning the access to stereoregular functionalized polyolefins, including synthetic strategies such as post-functionalization, chain transfer and direct copolymerization methods. The focus of the review lies in the copolymerization approach, in which various polar comonomers and versatile stereoselective polymerization catalysts based on both early and late transition metals are involved. Polymer properties and potential applications for these materials are simply discussed.1. Introduction2. Reactive-Intermediate-Polymer Approach to Stereoregular Functionalized Polypropylene3. Preparation of Stereoregular Functionalized Polypropylene by Chain-End Functionalization4. Stereoselective Copolymerization of Propylene and Polar Monomers by Early Transition Metal Catalysts5. Stereoselective Copolymerization of Propylene with Polar Monomers by Late Transition Metal Catalysts6. Stereoselective Copolymerization of α-Olefins with Polar Monomers7. Stereoselective Homopolymerization of Polar Monomers8. Polymer Properties and Potential Applications9. Conclusion and Outlook
Keywords: polypropylene; isotactic; stereoregularity; functionalized polyolefins; stereoselective polymerization; poly(α-olefin)s